Transformasi Konten dan Pola Siar Radio Madu FM dalam Meningkatkan Minat Pendengar di Era Digital - Febriany, Febriany; Putri, Pusparani Sahran; Maulana, Mohammad Iqbal; Rahmawati, Aninda; Afifah, Maulani (IAINU Kebumen, 2025)
This research is motivated by the phenomenon of the declining number of listeners of Madu FM Radio, especially among the digital generation, who began to switch from analog radio to digital platforms such as podcasts and streaming music. This change in media consumption patterns encourages Madu FM Radio to adapt to the needs and communication patterns of listeners in order to remain relevant and maintain audience loyalty. Theoretically, this research refers to Harold Lasswell's Communication Model and the concept of 7C's of Communication from Cutlip and Center (2006) to understand effective communication patterns and radio broadcast patterns, especially related to aspects of credibility, context, message content, clarity, continuity and consistency, communication channels, and audience capacity. This research uses a qualitative approach with descriptive methods to answer research questions related to communication patterns and broadcast patterns of Madu FM Radio in attracting and maintaining listeners' interest. Informants were selected using purposive sampling technique, consisting of broadcasters, content team, and active listeners of Madu FM Radio. Data collection techniques included observation of broadcast and content patterns, in-depth interviews, and documentation studies of broadcast data and listener interaction patterns. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the communication patterns and broadcast patterns of Radio Madu FM are in line with the concept of the 7C's of Communication and are reinforced by the theme of communication. Translated with DeepL.com (free version)